Tmem45b modulates itch via endoplasmic reticulum calcium regulation - Wang, Sa-shuang; Liang, Chen; Wang, Ruo-lin; Sun, Ze-lin; Ren, Peng-yu; Wu, Bin; Sun, Juan-juan; Fu, Li; Xiao, Li-zu; Sun, Wu-ping; Li, Chang-lin (Frontiers in Physiology, 2025)
ObjectiveThis study aimed to investigate the role of Tmem45b, a gene expressed in itch-associated Dorsal root ganglion (DRG) neurons, in the regulation of itch sensation.MethodsThe expression of Tmem45b was examined in DRG neurons. These neurons included Nppb-, Mrgpra3-, and Mrgprd-positive subtypes, which are known to mediate itch. Behavioral response to various pruritogens including β-alanine, chloroquine, histamine, serotonin, and N-met-LTC4 were assessed on Mrgprd-cre::Tmem45bflox/flox conditional knockout (cKO) mice. Chronic itch was evaluated using both atopic dermatitis-like and dry skin-like mouse models. To investigate intracellular calcium dynamics, calcium imaging was performed on dissociated DRG neurons. Additionally, bulk RNA-seq was conducted on DRG from Tmem45b cKO mice to assess transcriptomic changes. Serca1 expression and the calcium storage capacity of the endoplasmic reticulum (ER) were analyzed following Tmem45b deletion.ResultsTmem45b was found to be expressed in itch-associated DRG neurons. In Tmem45b cKO mice, scratching behavior was reduced in response to β-alanine but increased in response to chloroquine. Notably, chronic itch was alleviated in Tmem45b-deficient mice. Calcium imaging revealed that Tmem45b cKO impaired calcium responses to β-alanine and allyl isothiocyanate, but not to chloroquine. Mechanistically, Tmem45b deficiency led to a significant downregulation of Serca1, reducing ER calcium storage capacity. Pharmacological inhibition of Serca1 in DRG neurons similarly suppressed intracellular calcium release in response to β-alanine and chloroquine.ConclusionTmem45b plays a critical role in nonhistaminergic itch by regulating ER calcium homeostasis through Serca1. Its deficiency reduces itch behavior and impairs calcium signaling in DRG neurons, suggesting that Tmem45b is a potential therapeutic target for chronic itch.